ESTUDIO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA CAJA DE AHORRO PARA LOS ADJUDICATARIOS DEL CENTRO COMERCIAL 3 DE MAYO DEL CANTÓN SARAGURO, PROVINCIA DE LOJA - González Sarango., Edith Marlene (2019)
The degree work called: “FEASIBILITY STUDY FOR THE CREATION OF A SAVINGS BANK FOR THE AWARDS OF THE SHOPPING CENTER MAY 3 OF THE CANTÒN SARAGURO, PROVINCE OF LOJA”, aims to promote a financial culture to each of the people who They will be part of the savings account as partners, and in this way they can quickly access the products offered by the institution. In the present work, a descriptive-applied research was carried out with a quantitative and qualitative approach using methods such as: inductive, deductive and analytical; The study population was 51 people, where each of them carried out a technique that is the same survey that allowed to determine clearly and concisely what is the financial situation of each of the winners. For the fulfillment of this project, four studies were developed that are: Market Study, in this two important aspects that are supply and demand were defined; Likewise, in the Technical Study, the installed capacity, size, location, project engineering, process flowcharts, cash distribution, plant size and personnel requirements were determined. In the Administrative - Legal Study, a structural organization chart was developed, manual of functions considering the hierarchical levels so that the personnel to work in the box have clear their functions and responsibilities, on the other hand in the legal aspect the statute and regulation of the Savings Bank "May 3"; Finally, in regard to the Financial Study, it was found that the project is feasible, taking into account the financial evaluation that is classified in the following indicators: Positive Net Present Value (NPV) of $ $7.453,00; an Internal Rate of Return (IRR) of 31% that is higher than the Minimum Rate of Return (6.12%); a Capital Recovery Period that is 4 years 2 months 26 days and a Cost Benefit Ratio of 1.26 which means that for every dollar invested it will generate a profit of 26 ctvs., which means that the project for the Creating a savings account for the winners of the Mercado Comercial Centro 3 de Mayo is feasible.